A Bibliometrical Analysis of the Articles on Environmental Education Published between 1973 and 2019 - Muhammed Akif Kurtulus; Nilgun Tatar (Journal of Education in Science, Environment and Health)
The aim of the study is to conduct bibliometrical analysis of the published articles on environmental education. With this aim, 3979 articles published between 1973 and 2019 were reached as a result of scanning Scopus database and they were bibliometrically analyzed so that research tendencies in the last 46 years were determined. The database was scanned using “environment/environmental education” keywords and results regarding the annual distributions of the articles; the journals and the authors with the highest number of related articles; h-index scores of the authors; research collaboration networks; the articles that were cited at the highest rates; the average annual citation scores; the citation burst scores of the authors; the results for word cloud and the conceptual mapping patterns obtained were analyzed. The findings reveal that the issue started to gain popularity among scientific researchers after 2008. The journal publishing the highest number of articles on the topic is found to be Environmental Education Research while the researchers with the highest number of published articles belong to Kopnina, H., Bogner, F. X., and Thiengkamol, N. The researchers from Netherlands, Mexico and Israel have the highest rates of research collaborations. The related articles are found to focus mostly on sustainability education, climate change, teacher education, student’s or teacher’s attitudes toward environment, the level of knowledge and consciousness on environment and environmental issues. The most frequently used concept in the keywords sections of published articles is determined to be “environmental education”. The findings of the study are meant to guide researchers planning to conduct further research on the issue.